FORENSIC, CLINICAL AND SOCIAL ASPECTS IN A CASE OF A CHILD THAT SURVIVED AN ELECTRICAL TRAUMA - Atanas Christov; Teodora Kiryakova; Dimitar Nikolov; Biliana Mileva; Alexander Alexandrov (Science & Research)

(untitled)
Introduction: We present a case of a 10 year old child who has experienced electrical trauma while playing and climbing on wagons in an unguarded railway depot. After being struck by the electric arc the child was taken to the emergency. Four surgical interventions for auto-transplantation of skin were carried out for one whole month.Materials and methods: In the forensic examination and in the medical documentation, presented 3 months after the incident, we observed that there were extensive scars with the appearance of keloid on both legs and the right gluteal area. In addition there were scars on the left hand, extensive ones on both legs and the back from medical manipulations performed for auto-transplantation of skin tissue. The electrical burning affected 22% of his body, and the burnings were II and III degrees. Discussion: The scars on both legs provided a forensic conclusion that the electric arc has passed through the two lower limbs without damaging any internal organs. Furthermore, during the forensic examination, extensive scars to the degree of keloid were identified where skin has been removed for auto-transplantation. Conclusion: In social and life aspects, we consider that children should be made aware of the danger of approaching high-voltage cables, as well as there should be strict regulations and control on who enters railway depots.